The Emergency Dental Appointment: Restorative Emergencies Part 1 – Tooth Related Problems. Issue 2 (June 2017) - Rodriguez, Jose M; Kalsi, Harpoonam; Bavisha, Kalpesh; Darbar, Ulpee
Dental emergencies affect a large proportion of the population. While there is ample information in the literature on how to manage medical emergencies in dental practice, there is little information on common dental emergencies and how to manage them. In the UK, the 2009 Adult Dental Health Survey reported 9% of dentate adults reporting pain at their clinical examination. 1 The prevalence of non-pain related restorative dental emergencies is estimated to be higher, and will be a common presenting situation in the dental clinic. Often these unplanned events cause difficulties for dental practitioners, who are already constrained by time, to fit in these patients and manage them. Over and above this, the increasing life spans, retention of teeth into later life and finite life of dental restorations all add to the challenges encountered by the dental practitioner. Prompt and effective management of these conditions often leads to optimising patient experience, but also offers better outcomes. This two-part series provides an overview of the more common dental emergencies encountered by the dental practitioner and their management. Paper 1 focuses on the management of common tooth-related emergencies and includes non-odontogenic and odontogenic pain. Paper 2 focuses on the management of osseointegrated dental implant related emergencies.